Translation and global spaces of power - Baumgarten, Stefan; Cornellà-Detrell, Jordi (Blue Ridge Summit, PA : Multilingual Matters, 2018)
This book focuses on the role of translation in a globalising world. It presents a series of case studies that explore the ways in which translation is subject to ideology and power play across diverging domains and genres. Broadly based on a discussion of 'translation and the economies of power', the chapters examine an array of contextual and textual factors, ranging from global, regional and institutional power relations to the linguistic, stylistic and rhetorical implications of translation decisions. The book maps the multiple ways in which power relations and ideological positions affect cross-cultural communication, with special reference to repressive practices in history, translation policies, media power and commercial hegemonies. It concludes that future translation research will benefit from a more sustained emphasis on the power of technology and economic capital.
Frontmatter -- Contents -- Contributors -- Acknowledgements -- General Introduction -- Part 1. Translation and the Spaces of Power -- 1. Translation and the Economies of Power / Baumgarten, Stefan / Cornellà-Detrell, Jordi -- 2. Bloodless Academicians and the Power of Translation Studies / Pantuchowicz, Agnieszka -- 3. Turning Minorities and Majorities Upside Down / Doorslaer, Luc van -- Part 2: Domination and Hegemony in History -- 4. Where the Devil Sneaks In: Power and Agency in Radical Bible Translation / Bennett, Karen -- 5. Challenging the State: Subversive Welsh Translators in Britain in the 1790s / Löffler, Marion -- 6. The Greek-Turkish Population Exchange: Reverberations of a Historical Experience Through Translation / Sidiropoulou, Maria / Albachten, Özlem Berk -- 7. Translation Choices as Sites of State Power: Gender and Habitus in Bestsellers in Franco's Spain / Castro, Cristina Gómez -- Part 3. Media Translation in the Global Digital Economy -- 8. Translation and Mass Communication in the Age of Globalisation / Lambert, José -- 9. Power Complexity in Translated Political Discourse / Schäffner, Christina -- 10. Proximisation Amidst Liquidity: Osama bin Laden's Death Translated / Caimotto, M. Cristina -- Part 4: Commercial Hegemonies in the Global Political Economy -- 11. Translation and Interpreting for the Media in the English Premier League / Baines, Roger -- 12. How Global Conglomerates Influence Translation Practice: Film Title Translation in Turkey / Ross, Jonathan -- 13. Translated Chinese Autobiographies and the Power of Habitus in the British Literary Field / Meng, Pei -- Conclusion: Translation, Power and Social Justice -- Index
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Translating and interpreting -- Social aspects; Intercultural communication; Communication interculturelle; FOREIGN LANGUAGE STUDY -- Multi-Language Phrasebooks; LANGUAGE ARTS & DISCIPLINES -- Alphabets & Writing Systems; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; LANGUAGE ARTS & DISCIPLINES -- Readers; LANGUAGE ARTS & DISCIPLINES -- Spelling; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting; Intercultural communication; Translating and interpreting -- Social aspects